Porphyrin-based metal–organic framework thin films for electrochemical nitrite detection - Kung, Chung-Wei; Chang, Ting-Hsiang; Chou, Li-Yao; Hupp, Joseph T.; Farha, Omar K.; Ho, Kuo-Chuan (Electrochemistry communications, 2015)
Uniform zirconium-based porphyrin metal–organic framework (MOF-525) thin films are grown on conducting glass substrates by using a solvothermal approach. The obtained MOF-525 thin film is electrochemically addressable in aqueous solution and shows electrocatalytic activity for nitrite oxidation. The mechanism for the electrocatalytic oxidation of nitrite at the MOF-525 thin film is investigated by cyclic voltammetry. The redox mechanism of the MOF-525 thin film in the KCl aqueous solution is studied by amperometry. The MOF-525 thin film is deployed as an amperometric nitrite sensor. The linear range, sensitivity, and limit of detection are 20–800μM, 95μA/mM-cm2, and 2.1μM, respectively. [Display omitted] •Zirconium-based porphyrin MOF thin films are grown on conducting substrates.•The MOF-525 thin film shows electrocatalytic activity for nitrite oxidation.•Redox and electrocatalytic mechanisms of the MOF thin film are investigated.•The amperometric nitrite sensor using MOF-525 thin film is successfully developed.